Dampak Peningkatan Operating Leverage dan Financial Leverage terhadap Profitabilitas pada Perusahaan Industri Barang Konsumsi - Tresna Pratiwi; Dimas Sumitra Danisworo; Mochamad Edman Syarief (Indonesian Journal of Economics and Management, 2022)
The purpose of this research are to know the influence of Operating Leverage and Financial Leverage to Profitability in Consumer Goods Industrial Companies listed on IDX for 2015-2019 period. The data used in this research is secondary data that is obtained indirectly from annual report contained on the IDX from 2015-2019. The population in this research are 53 Consumer Goods Industrial Companies listed on IDX in 2015-2019. The research sample was 8 companies using purposive sampling technique. The analytical method used in this research is multiple linear regression analysis using the IBM SPSS 25 application tool. Based on the F test, it is known that simultaneously DOL and DFL affect on profitability. Based on the results of the t test, it is known that operating leverage partially has no effect on profitability and partially financial leverage has a significant negative effect on profitability.